Mold Strength Analysis of Press Machine Composite Brake Using FEM Method on Train Brakes - Andhika Muhammad Kasyafa; Muhamad Juan Raffindo; Nuha Desi Anggraeni (METAL: Jurnal Sistem Mekanik dan Termal, 2022)
Press machine is a mechanism that works by compressing objects. It is powered by hydraulic machines, electric motors, or human power. Usually in the railway industry, presses are used in the manufacture of composite brake pads for railways. This study was conducted to find out how strong the mold of the composite brake press machine is if given the maximum load by hydraulics, this study also analyzes the mold of the press machine which plays an important role in the manufacture of composite brake linings using the Finite Element Methods (FEM). Therefore, the mold of the press must have sturdy characteristics and can withstand a lot of loads so that the structure will not deform while the process is in progress. The conclusion is that the maximum voltage amount in the mold is 33,596,928 N/m2 (using ASTM A36 as the reference material) which does not cause major deformation of the mold and is still considered safe.